Design of a sound pressure level acquisition and analysis system - Casas, Julian F.; Noreña, Paula T.; Hermida, Luís F. (TECCIENCIA, 2014)
This study focuses on the development of an analysis and acquisition software for sound pressure levels in industrial areas, designed and optimized to comply with the requirements of international standard ISO 7731 (“Danger Signals for Public and Work Areas” [1]) by performing a study of octave band equivalent sound pressure levels from 125 Hz to 8 KHz. The software and algorithms proposed are linked with other codes to perform a complete analysis for the above standard. The software we outline focuses on the capture process for subsequent analysis and can be applied not only for application with ISO 7731 [1] but also for the acquisition of equivalent sound pressure levels in any field of study. However, one needs to bear mind that the hardware used in data acquisition must comply with quality requirements and may directly cause systematic errors in the results. The main achievement of this study is the use of acoustic theory (as taught in university) to develop high-quality data acquisition systems that can be applied in academic projects and research projects, thus removing an obstacle in scientific and engineering development.